Тепловое диагностирование трубопроводов - Костина, Н. А. (ХНУРЭ, 2012)
Results of IR investigation of high pressure pipes with heating in South-Ukrainian atomic power plant are presented. Procedure of detecting of defects of thinning type is described. Difference of temperature in different zones amounted 11ºC. Obtained results show the advantages of IR method for detecting of thinning in the high pressure pipes.
Keywords: трубопровод; тепловое диагностирование